Glove and mitten protection in extreme cold weather: an Antarctic study. Issue 1 (31st January 2016) - Iserson, Kenneth V.
Abstract : Background: Myths, misconceptions and a general lack of information surround the use of gloves and mittens in extreme cold environments. Objective: This study assessed how well an assortment of gloves and mittens performed in a very cold environment. Methods: A convenience sample of gloves and mittens were tested in Antarctica during the winter of 2016 using a calibrated thermometer (range: −148°F to +158°F/−100°C to +70°C) three times over a 0.5-mile distance (~20 minutes). A small sensor on a 10-foot-long cable was taped to the radial surface of the distal small finger on the non-dominant hand. The tested clothing was donned over the probe, the maximum temperature inside the glove/mitten was established near a building exit (ambient temperature approximately 54°F/12°C), and the building was exited, initiating the test. The hand was kept immobile during the test. Some non-heated gloves were tested with chemical heat warmers placed over the volar or dorsal wrist. Results: The highest starting (96°F/36°C) and ending (82°F/28°C) temperatures were with electrically heated gloves. The lowest starting temperature was with electrically heated gloves with the power off (63°F/17°C). Non-heated gloves with an inserted chemical hand warmer had the lowest minimum temperature (33°F/1°C). Maximum temperatures for gloves/mittens did not correlate well with their minimum temperature. Conclusions: Coverings that maintained finger temperatures within a comfortable and safe range (at or above 59°F/15°C) included the heated gloves and mittens (including some with the power off) and mittens with liners. Mittens without liners (shell) generally performed better than unheated gloves. Better results generally paralleled the item's cost. Inserting chemical heat warmers at the wrist increased heat loss, possibly through the exposed area around the warmer.